The histopathological and functional consequences of microplastic exposure - Yujeong Lee; Minkyoung Sung; Soo-Eun Sung; Joo-Hee Choi; Kyung-Ku Kang; Jae Woo Park; Ye-jin Kim; Sijoon Lee (Discover Applied Sciences)
Abstract As the production, usage, and disposal of plastics increase, the microplastics generated—plastic particles smaller than 5 mm—increases, exacerbating environmental pollution. In turn, various organisms become increasingly exposed to contaminated environments, potentially affecting humans through the food chain. Crucial findings from in vivo experiments indicate histopathological changes caused by microplastics impact the morphology and physiological function of organisms. This study describes the histopathological changes induced by microplastics across the circulatory, nervous, digestive, respiratory, and reproductive systems and explains associated functional alterations. Except in the nervous system, the main morphological changes involve degenerative changes throughout the body, such as apoptosis, inflammation, and fibrosis. Most changes were induced by inflammatory responses to microplastics, leading to fibrosis and subsequent functional impairments. Various studies confirm that microplastics stimulate cells, leading to increased reactive oxygen species production, inflammation, and cell death. Consequently, these morphological changes impair related systemic functions. This review highlights fundamental morphological changes in organs and cells due to microplastics and discusses the limitations involving systems showing no changes.